2008
DOI: 10.1111/j.1442-200x.2007.02496.x
|View full text |Cite
|
Sign up to set email alerts
|

Relation of ferritin levels with symptom ratings and cognitive performance in children with attention deficit–hyperactivity disorder

Abstract: Background-The aim of the present paper was to investigate the relationship between behavioral symptoms and attentional and executive functions and hematological variables related to iron deficiency and anemia, ferritin, hemoglobin, mean corpuscular volume (MCV), and red cell distribution width (RDW) in children and adolescents with attention deficit-hyperactivity disorder (ADHD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
55
2
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 29 publications
13
55
2
1
Order By: Relevance
“…Decreased ferritin has been associated with other psychiatric disorders, such as attention deficit-hyperactivity, schizophrenia and major depression. [30][31][32] Studies have described direct proinflammatory effects of iron deficiency on macrophages and foam cells. 33 Other methods can be used to estimate cellular iron stores in patients.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased ferritin has been associated with other psychiatric disorders, such as attention deficit-hyperactivity, schizophrenia and major depression. [30][31][32] Studies have described direct proinflammatory effects of iron deficiency on macrophages and foam cells. 33 Other methods can be used to estimate cellular iron stores in patients.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have focused on the utility of iron supplementation in ADHD, with conflicting results [11]. One study investigated the relationship between iron levels and cognitive functioning of children with ADHD [12]. Results of that study reported no significant correlations between ferritin level and performance in vigilance and sustained attention tasks, executive function tests like planning and organization, complex problem solving, set shifting and response monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, these children exhibit more anxiety, depression, and social problems, and show an impaired prolactin response to stress, long after iron repletion (Lozoff et al 2000;Felt et al 2006). ID indicated by low serum ferritin concentration has been linked to the severity of attention-deficit/hyperactivity disorder (ADHD) and resistance to psychostimulant treatment (Konofal et al 2004Oner et al 2008;). Moreover, low mean corpuscular volume (a marker of ID) at *3 years of age has been associated with reduced response to psychostimulants nearly 3 years later (Turner et al 2012).…”
mentioning
confidence: 99%